The interrelationship between genotype, sex, and dietary lysine effecfs on growth performance and Protin accretion in finishing pigs fed to 230 and 280 lb - Friesen, K.G.; Kats, L.J.; Hansen, J.A.; Laurin, J.L.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred and twenty pigs (initially 96 lb BW) were used to determine the interrelationship between genotype, sex, and dietary lysine effects on growth performance and carcass composition in a 2 x 2 x 2 factorial arrangement. Genetic comparisons were made between pigs characterized by either high or medium potential for lean tissue gain. Within genotype, barrows and gilts were separately fed either a .90 or a .70% lysine diet until the mean weight of pigs in each pen of three reached 230 lb. One pig per pen was then slaughtered to determine carcass characteristics and chemical composition. From 230 to 280 lb, dietary lysine was lowered to .75 or .55% for pigs fed .90 or .70%dietary lysine, respectively. When the pig mean weight met or exceeded 280 lb, both pigs were slaughtered to determine carcass characteristics and chemical composition. The right side of the carcass was then ground and chemically analyzed to determine protein and lipid accretion rates. No interactions were detected; therefore, main effect means will be discussed. At 230 lb, high lean-gain pigs had increased ADG and gain to feed ratio compared to medium lean-gain pigs. Barrows had increased ADG and ADFI, but exhibited a poorer feed to gain ratio than gilts. Pigs fed .90% lysine had improved ADG compared to pigs fed .70% lysine. High lean gain pigs had increased CP accretion and lipid accretion compared to medium lean-gain pigs. Similarly, gilts had increased CP accretion and decreased lipid accretion compared to barrows. Cumulative ADG (96 to 280 lb) was greater for high lean gain pigs, barrows, and pigs in the .90/.75% lysine regimen. Average daily feed intake was increased in barrows compared to gilts. Gilts had greater CP accretion than barrows. Crude protein accretion was greater in high lean gain pigs compared to medium lean-gain pigs, with high lean gain gilts having the greatest magnitude of response to increased dietary lysine. High lean-gain pigs exhibited greater growth performance and CP accretion compared to medium-lean pigs, with high lean-gain gilts offering the largest potential for maximized lean tissue accretion and improved lean efficiency.
Keywords: Swine; Pigs; Lysine; Sex; Carcass composition; Genotypes